Omniscient reader's viewpoint. 03 - Umi (Korean author at Redice Studio); Singsyong; Torres, J., 1969- (Ize Press, 2024)
"If you have a shred of pride left, stand up and fight! Inside the ruthless scenarios of TWSA, something as simple as getting a meal is a life-or-death struggle. With all the food destroyed by the goblin, Dokja's group is forced to venture into the dark tunnels full of vicious creatures. But in the cruel new world, monsters are not the most dangerous enemies...Fear and desperation among the survivors cause Geumho Station to erupt into wanton bloodshed. And amid the chaos, Huiwon's true power awakens--the Time of Judgment is here!"--